2011
DOI: 10.1007/s10620-011-1680-4
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Intestinal Metaplasia After Successful Eradication of Barrett’s Esophagus with Radiofrequency Ablation

Abstract: Background Radiofrequency ablation (RFA) is an effective means of eradicating Barrett's esophagus (BE), both with and without associated dysplasia. Several studies have documented high initial success rates with RFA. However, there is limited data on IM detection rates after eradication. Aims To determine the rate of detection of intestinal metaplasia (IM) after successful eradication of Barrett's esophagus. Methods BE patients with and without dysplasia who had undergone RFA were retrospectively identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 14 publications
7
69
0
2
Order By: Relevance
“…Importantly, these authors detected dysplasia at the time of recurrence in four patients. Despite the lack of direct biomarker evidence, these studies suggest that RFA may not eliminate the risk of progression to cancer in all patients [92], an outcome consistent with clinical data from a randomized trial of RFA ablation vs.…”
Section: Clinical Evidence After Radiofrequency Ablationsupporting
confidence: 58%
“…Importantly, these authors detected dysplasia at the time of recurrence in four patients. Despite the lack of direct biomarker evidence, these studies suggest that RFA may not eliminate the risk of progression to cancer in all patients [92], an outcome consistent with clinical data from a randomized trial of RFA ablation vs.…”
Section: Clinical Evidence After Radiofrequency Ablationsupporting
confidence: 58%
“…A major problem limiting the conclusions that can drawn from these reports is that they do not describe specifically how frequently biopsy specimens contained sufficient subepithelial lamina propria to be informative for buried metaplasia [63] . A different result was found by Vaccaro et al [64] who performed a retrospective analysis of patients with BE who underwent RFA. The cumulative incidence of newly detected intestinal metaplasia at 1 year was 25.9%.…”
Section: Hgdmentioning
confidence: 69%
“…In contrast, one recent study by Vaccaro et al [35 ]of 47 patients who had RFA with apparent complete eradication of intestinal metaplasia found recurrent metaplasia in 15 patients (32%) during a follow-up period ranging from 5 to 38 months. Follow-up endoscopic procedures in this study included taking four biopsy specimens from columnar epithelium at the gastroesophageal junction (GEJ) just distal to the neosquamocolumnar junction.…”
Section: Rfa For Nondysplastic Barrett's Metaplasiamentioning
confidence: 86%
“…During surveillance colonoscopy, however, recurrent polyps are visible lesions that are removed immediately. After RFA for Barrett's esophagus, Vaccaro et al [35] showed that intestinal metaplasia can recur in almost one third of patients within 3 years and, in most cases, this recurrence is not visible and is detected only as the result of biopsy sampling at the GEJ. Does this mean that patients with recurrent metaplasia in those biopsy samples will require another endoscopy to administer more RFA, and perhaps another endoscopy after that to document that the recurrent metaplasia was eradicated?…”
Section: Rfa For Nondysplastic Barrett's Metaplasiamentioning
confidence: 99%